Kreativitas Dan Kritis Dalam Pendidikan Seni di Sekolah dan Keluarga - Panggabean, Ance (Visi Sosial Humaniora, 2024)
Current developments in technology and art have an impact on creativity and critical thinking which has brought major changes to arts education. The new paradigm includes the integration of technology in the arts curriculum, as well as the use of new media for artistic expression and creative learning. A holistic approach to artistic values ​​also makes this paradigm encourage art teaching that considers environmental impacts, as well as promoting awareness of environmental issues through works of art. Arts education remains sustainable over a long period of time, without destroying the environment so that it can continue to offer a good artistic life for every individual. Assessment of artistic creativity in a learning context is an assessment that accommodates process and outcome aspects. Evaluation of arts education in assessing learning as creative education. The teacher's task is to assess student creativity starting from the learning process to the learning outcomes, because creativity is a process that is inherently related to reflection on a person's self-development process.